Premature Hair Graying: Underlying Contributors and Management Approaches - An Updated Literature Review - Libera, Anna; Kostro, Julia Maria; Makulec, Gabriela; Bartkewicz, Karolina; Papież, Magdalena; Jędra, Zofia; Domosud, Karolina; Novik, Lizaveta; Kozicki, Maciej Jakub; Zienkiewicz, Damian (Quality in Sport, 2026)
Background: Premature hair graying (PHG) is considered a distinct clinical entity, in which the presence of grey hairs on the scalp appears at a young age, generally before 20 years of age in individuals of European descent or slightly later, before 30 years of age in individuals of African ancestry. The etiology of premature hair graying remains multifactorial. Aim of the study: The objective of this narrative review was to summarize the potential contributors, which may play a role in graying of the hair at the young age. Material and methods: This comprehensive narrative literature review was conducted based on the scientific literature retrieved from the PubMed database. The analysis included original studies and case reports, which had been concentrated on the occurrence of PHG. Results: The available literature suggests correlations between premature canities and nutrient deficiencies in cobalamin, copper, folic acid, biotin, iron, calcium, zinc, cholecalciferol. The positive association with PHG indicate also high level of oxidative stress, long-term emotional stress, tobacco smoking, genetic disorders, autoimmune diseases or just be a side effect of some medications. Conclusions: The etiology of PHG is multifactorial. To date no effective therapeutic method capable of reversing premature hair graying has been established, highlighting the need for further research.